Rainfall redistribution in a mixed forest fragment in Durango, Mexico - Ramos Hernández, César Gerardo; González Rodríguez, Humberto; Domínguez Gómez, Tilo Gustavo; Corral Rivas, Sacramento; Luján Soto, José Encarnación; Gómez Meza, Marco Vinicio (Ecosistemas y Recursos Agropecuarios, 2025)
In order understand the redistribution of precipitation in a fragment of mixed forest in the “Ejido” Adolfo Ruiz Cortines, Durango, an experiment was conducted between 2017 and 2020 at a 2500 m2 forest plot, where the interception and water flow of precipitation, throughfall, and stemflow were measured to quantify losses due to canopy interception and to characterize the chemical properties of water (pH (CaCl2) and CE (μS cm-1)). A total of 77 rainfall events were recorded, with a precipitation of 2,236.1 mm. Throughfall for Arbutus bicolor, Quercus rugosa, and Q. sideroxyla was 63%, 82%, and 76%, respectively. Stemflow accounted for 0.08% in A. bicolor, 0.41% in Q. rugosa, and 0.88% in Q. sideroxyla. Interception losses were 34%, 18%, and 17% for A. bicolor, Q. rugosa, and Q. sideroxyla, respectively. The chemical analysis of rainwater showed a pH mean of 5.9 for precipitation, decreasing to 5.6 for throughfall and remaining at 6.0 for stemflow. Electrical conductivity values were 32.4 for precipitation, 39.63 for throughfall, and 116.04 for stemflow. Understanding water interception is crucial to recognizing that, from a hydrological perspective in forest management, the presence and distribution of plant species are essential to ensure adequate water flow in the ecosystem, a key aspect for maintaining active biogeochemical processes.
Keywords: forest ecosystem; stemflow; flow; interception